RASopathies: From germline mutations to somatic and multigenic diseases - Quentin Riller (Biomedical Journal, 2021)
The RAS-RAF-MEK-ERK signaling pathway is vital for different cellular mechanisms including cell proliferation, differentiation and apoptosis. This importance is highlighted by the high prevalence of mutations in RAS or related proteins of the pathway in cancers. More recently, development abnormalities have been linked to various germline mutations in this pathway and called RASopathies. Interestingly, rare disorders such as RAS-associated leukoproliferative diseases and histiocytosis have also been recently linked to multiple mutations in the same pathway, sometimes with the same mutation. This review will focus on germline RASopathies and rare somatic RASopathies and focus on how gain-of-function mutations in the same pathway can lead to various diseases.